SISTEM PENANAMAN LEGUME COVER CROP PADA LAHAN REPLANTING PERKEBUNAN KELAPA SAWIT - Yohana Theresia Maria Astuti; Tri Nugraha Budi Santosa; Andi (AGROISTA : Jurnal Agroteknologi, 2018)
The objectives of this study were to determine the effectiveness of LCC planting methods on replanting areal and to determine the best growth of LCC between lining, digging and broadcasting methods. This research was conducted in Ukui sub-district, Pelalawan district, Riau. This research was conducted by experimental method which was arranged in Randomized Complete Block Design (RCBD). The first factor is the method of planting which consists of lining system, digging system and broadcasting system. The second factor is land condition which consists of hilly area, flat area and low area. Each treatment combination with 3 replications. The data of the research were analyzed by analysis of variance at level of 5%. If there is a real difference, then tested by DMRT at 5% confidence level. The results showed that planting system gave the same effect to LCC growth. While the best condition of land for LCC growth is on flat area and low area than hilly area. Keywords : Lining, digging, broadcasting, hilly area, flat area, low area, LCC